Validitas Prediktif Papi-Kostick dan Baum terhadap Pengendalian Emosi Karyawan - Savira, Alice Whita; Hidayat, Rahmat (Jurnal Psikologi, 2017)
The availability of quality human resources was important for the continuity excellence of the company and for gaining competitive advantage in the company. It could be obtained by operationalizing development or placement as part of HR management practices based on a potential review. This led to the use of psychological tests. The accuracy of psychological tests was required in potential review in order to predict future behavior. HR practitioners and psychologists showed appreciation and confidence in psychological tests. However, it had not been fully supported by empirical evidence regarding the accuracy of the tests for selecting employees. The purpose of this study was to figure out the extent of both tools in predicting emotion control. The finding from 159 subjects showed that the activity factor PAPI-Kostick and crown of tree predicted the emotion control.Abstrak : Untuk kesinambungan kinerja perusahaan dan capaian keuntungan kompetitif, diperlukan manajemen SDM potential review. Potential review memerlukan peran alat tes psikologi yang akurat untuk memprediksi perilaku. Apresiasi dan kepercayaan psikolog pada alat tes psikologi belum didukung oleh bukti-bukti empiris (evidance based) mengenai hal tersebut. Tujuan penelitian ini untuk melihat sejauh mana PAPI-Kostick dan BAUM mampu memprediksi pengendalian emosi. Hasil penelitian pada 159 karyawan, menunjukkan faktor aktivitas PAPI-Kostick dan bagian mahkota pada BAUM dapat memprediksi pengendalian emosi. Sehingga efektivitas penggunaan kedua alat tes psikologi tersebut untuk mengases potensi pengendalian emosi karyawan.